Impactos da burocracia no trabalho docente no Estado de Minas Gerais sob o governo Romeu Zema - Cazetta, Aline Mariane (2022)
This text analyzes the impacts of bureaucracy on teaching work; how it impacts individual work and the operating structure of State Schools in Minas Gerais. The results obtained are the analysis of the contradictions between what is proposed in the documents and the effective practice of everyday school life, supported by a Marxist theoretical basis. My hypothesis is that bureaucracy is used as a rigid means of control, supervision and alignment of the institution with practices linked to the political projects of the Romeu Zema government (New Party), linked to the managerial reform that takes place in the field of education. In this way, there are indications that the bureaucracy is designed to function to meet the demands of control and power, being efficient for the systematic collection of data, to the detriment of the improvement of educational practice.